PENGARUH PENGUMUMAN STOCK BUYBACK TERHADAP REAKSI PASAR PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2019 - Qonita Zein; Taufiq Akbar (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT This study aims to analyze the effect of share buyback announcements on the market reactions in companies listed at Indonesia Stock Exchange (ISE) within the year of 2016-2019. This study consisted of 32 samples of companies from all sectors listed on the Indonesia Stock Exchange (ISE) and made share buyback announcements. The data used in this study are secondary data in the form of stock prices and stock trading volume and the sample selection method uses purposive sampling method. The analytical method used in this research is the event study. The data analysis technique used for this study was the Kolmogrov-Smirnov normality test, followed by a paired sample t-test for hypothesis 1 and hypothesis 2 with a significance level of 0.05. The results of this study indicate that there is a significant influence on the average abnormal return variable, but there is no significant effect on the variable average trading volume activity beforeand after the announcement of stock buybacks. Keywords: Buyback, Abnormal Return, Trading Volume Activity.